Sustainable Amylopectin‐Derived Miniwindmills for Moisture‐Induced Electric Generation. Issue 11 (16th September 2022) - Sun, Bianjing; Xu, Dan; Wang, Zengbin; Pang, Bo; Wang, Jiaxiu; Sun, Dongping; Zhang, Kai
Abstract : Capturing energy from the environment provides the hope for clean energy and enables the formation of self‐powered systems. Nanostructured functional materials can interact with water to generate electrical energy, greatly expanding the technical capabilities of water energy harvesting, while those derived from sustainable biomass for this purpose are still in the infancy. Herein, a series of thin self‐standing amylopectin‐derived membranes of several micrometers can output hydrovoltaic electric energy in the ambient environment. One single‐unit flat device (around 0.78 cm 2 ) can generate an instant voltage of up to 0.95 V from high ambient humidity. The underlying mechanism for generating electricity from amylopectin‐derived membranes is attributed to the fast adsorption and desorption of water molecules on the membrane surface based on the results of dynamic vapor sorption. Novel moisture‐induced miniwindmills as electric generators are fabricated, thanks to these outstanding features such as being self‐standing, flexible, lightweight, and having ease of scale production. Such miniwindmill devices with a membrane layer thickness of ≈10 μm can be used to harvest energy with a sustained voltage of around 0.45 V from ambient environment. These results pave the way for developing energy‐harvesting powerful minisized devices that exploit water gradients prevalent in nature with biomass materials. Abstract : Herein, flexible and self‐standing amylopectin‐derived membranes with excellent mechanical performance and high‐electricity‐output performance under the stimulus of humidity are developed. As‐designed miniwindmill generators can produce a sustained 0.45 V. Most importantly, herein, the foundation is laid for expanding the new application range of biomass‐based smart electricity generators.